2012
DOI: 10.1590/s1982-56762012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of isolates of Ralstonia solanacearum biovar 2, pathogenic to Eucalyptus "urograndis" hybrids

Abstract: The objective of this study was to characterize isolates of biovar 2 of Ralstonia solanacearum pathogenic to eucalyptus "urograndis" hybrid by means of biochemical tests, as well as evaluation of host range and identification by PCR with primers for species, biovar and phylotype. Carbohydrate utilization assays revealed that the eucalyptus isolates belong to phenotype Tropical of biovar 2 (2T). From artificial inoculations it was possible to reproduce symptoms or recover the bacterium from: eucalyptus, potato,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
(12 reference statements)
2
6
0
6
Order By: Relevance
“…These results coincide with reports by Perea et al (2011), who reported that the growth of R. solanacearum colonies in a TTC growth media are characterized by a red color with white edges. The Gram staining and biochemical tests for oxidase, catalase, urease, coincide with reports by Yabuuchi et al (1995), Denny and Hayward (2001), Dhital (2001), EPPO (2004), Rahman et al (2010), Perea et al (2011), Marques et al (2012) and Rodríguez (2012) (Table 1).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…These results coincide with reports by Perea et al (2011), who reported that the growth of R. solanacearum colonies in a TTC growth media are characterized by a red color with white edges. The Gram staining and biochemical tests for oxidase, catalase, urease, coincide with reports by Yabuuchi et al (1995), Denny and Hayward (2001), Dhital (2001), EPPO (2004), Rahman et al (2010), Perea et al (2011), Marques et al (2012) and Rodríguez (2012) (Table 1).…”
supporting
confidence: 87%
“…La tinción de Gram y pruebas bioquímicas de oxidasa, catalasa, ureasa coincide con lo reportado por Yabuuchi et al (1995), Denny y Hayward (2001), Dhital (2001), EPPO (2004), Rahman et al (2010), Perea et al (2011), Marques et al (2012 y Rodríguez (2012) (Cuadro 1). Se caracteriza a la marchitez y pudrición basal de Jatropha curcas en Arriaga, Chiapas, México con síntomas de flacidez de pecíolos, marchitamiento y caída de hojas; pudrición de raíz y base del tallo, producción de raíces adventicias y senot fulfilled, this is the first report on the relation of Ralstonia solanacearum in wilting and basal rotting of the physic nut plant in Chiapas, Mexico.…”
Section: Figuraunclassified
See 1 more Smart Citation
“…Sua gama de hospedeiras ainda não é bem defi nida, pois mudanças na sistemática agrícola e no comércio global de mudas e sementes têm levado ao aparecimento de novas hospedeiras para isolados evasivos desse patógeno (TSUCHIYA, 2004). Um exemplo disso foi o ocorrido em 2009, quando a Raça 3 biovar 2T (R3bv2T) da bactéria foi relatada pela primeira vez, infectando um cultivo inicial do híbrido "urograndis" (Eucalyptus urophylla x Eucalyptus grandis), no município de Alexânia -Goiás (MARQUES et al, 2012). No Brasil, em infecção natural, a murcha bacteriana ocorre devido a biovar 1 e, nos demais países, pela biovar 3.…”
Section: Introductionunclassified
“…A murcha bacteriana causada pela bactéria Ralstonia solanacearum é uma das principais doenças que afetam a batateira no mundo (CARVALHO et al, 2017). O patógeno, nativo de solos, infecta a planta através das raízes e pode desencadear a perda total da produção da cultura da batata (MARQUES et al, 2012). O elevado tempo de sobrevivência no solo e a ampla gama de hospedeiro da R. solanacearum dificultam o controle da doença (CARVALHO et al, 2017;WU et al, 2014).…”
Section: Influence Of the Potato Production System On Soil Suppressivunclassified